Comprehensive Risk Evaluation of Perfluoroalkyl Substance Pollution in Urban Riverine Systems: Ecotoxicological and Human Health Perspectives - Ferlian Vida Satriaji; Cat Tuong Le Tong; Nelly Marlina; Yan Lin; Nguyen Duy Dat; Ha Manh Bui; Yoshifumi Horie; Jheng-Jie Jiang (Toxics)
This study investigated the spatiotemporal distribution of perfluoroalkyl substances (PFASs) in the Daku River, Taoyuan, with a particular focus on source apportionment and associated ecological and human health risks. The total PFAS concentrations ranged from below the detection limits to 185 ng/L, with perfluorooctanoic acid (PFOA) emerging as the predominant compound, followed by perfluorobutanesulfonic acid (PFBS). Elevated PFAS levels were observed downstream of the confluence between the Daku River and Litouzhou ditch, suggesting contributions from industrial activities. Principal component analysis (PCA) and positive matrix factorization (PMF) were employed to identify important components and factors that explain different compounds. Factor 1 (dominated by PFUnA) was attributed to sources such as food packaging and textiles. Factor 2 (PFBS, PFHxS, PFOS) originated from agricultural inputs and wastewater discharges linked to the semiconductor and photonics industries. Factor 3 (PFOA, PFNA, PFDA) was primarily associated with fluoropolymer manufacturing, electronics, chemical engineering, machinery, and coating production. Ecological risk assessments showed no significant threats (RQ < 0.1) for PFBS, PFPA, PFNA, PFOS, and PFDA. Human health risk evaluations based on the Health Risk Index (HRI < 1), likewise, indicated negligible risk from crop and vegetable consumption in the Daku River area. These findings underscore the importance of continued monitoring and targeted pollution management strategies to safeguard environmental quality and public health.